2008
DOI: 10.1021/np800221b
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Trends in the Dereplication of Natural Product Extracts. 2. The Isolation of Chrysaibol, an Antibiotic Peptaibol from a New Zealand Sample of the Mycoparasitic Fungus Sepedonium chrysospermum

Abstract: By the application of an HPLC bioactivity profiling/microtiter technique in conjunction with capillary NMR instrumentation and access to the AntiMarin database the conventional evaluation/isolation dereplication/characterization procedures can be dramatically truncated. This approach is illustrated using the isolation of a new peptaibol, chrysaibol (1), from a New Zealand isolate of the mycoparasitic fungus Sepedonium chrysospermum. The unique nature of chrysaibol was recognized by bioactivity-guided fractiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
41
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 15 publications
2
41
0
Order By: Relevance
“…Alamethicin, an archetypical peptaibol, was eightfold less potent than 1 against PANC-1 cells (SI Appendix, Table S19). This agrees with widely reported cytotoxic properties described for most known peptaibols (18)(19)(20)(21)(22)(23)(24)(25). To provide an overall better understanding of the antiproliferative and cytotoxic properties of 1, the 10 helix is shown that was generated with Φ-and Ψ-angles of −49°and −29°for poly-Ala dodecamer using the PepMake 1.2 server at pepmake.wishartlab.com/.…”
supporting
confidence: 81%
See 2 more Smart Citations
“…Alamethicin, an archetypical peptaibol, was eightfold less potent than 1 against PANC-1 cells (SI Appendix, Table S19). This agrees with widely reported cytotoxic properties described for most known peptaibols (18)(19)(20)(21)(22)(23)(24)(25). To provide an overall better understanding of the antiproliferative and cytotoxic properties of 1, the 10 helix is shown that was generated with Φ-and Ψ-angles of −49°and −29°for poly-Ala dodecamer using the PepMake 1.2 server at pepmake.wishartlab.com/.…”
supporting
confidence: 81%
“…The peptaibols have been intensively studied because of their abilities to form pores in the outer membranes of cells; these pore-forming capabilities result in most compounds in this class exhibiting nonspecific cytotoxic properties toward bacterial, fungal, and mammalian cells (15,17). The effects of peptaibols on mammalian cells tend to be relatively modest, causing the loss of cell viability at concentrations in the mid-to-high micromolar range (18)(19)(20)(21)(22)(23)(24)(25). With many hundreds of peptaibols reported, finding new peptaibol analogs that possess an alternative mode of biological activity would be an impracticable prospect if one relied solely on either chemically driven or genome-based approaches to identify candidate molecules.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…149 By this method, they isolated a new peptaibol chrysaibol, from a New Zealand isolate of the mycoparasitic fungus Sepedonium chrysospermum. 150 It is worthy to note that the method developed by Munro et al will be effective for crude extract evaluation, isolation and dereplication.…”
Section: Biodiversity Of Microbial Productsmentioning
confidence: 99%
“…Owing to the ubiquity and biodiversity of their producers, we predict that a myriad of new sequences of peptaibiotics will be discovered within the next decade! Note Added in Proof: Applying a novel screening approach, which combines HPLC/bioactivity profiling-microtiter plate fractionation with subsequent capillary NMR analysis [225], a new 15-residue peptaibol, chrysaibol, from the fungicolous strain CANU E609 was characterized. The producer has been isolated from a decaying fruiting body found in the Kamai Ranges near Kaitaki, Bay of Plenty, New Zealand, and reported as Sepedonium chrysospermum [226].…”
mentioning
confidence: 99%